Quantitative modeling of M&A success probability: Integrating macroeconomic volatility and temporal factors through survival analysis - Dan Xu (Journal of Economy and Technology)
This paper delves into the intricate dynamics of the likelihood of merger and acquisition (M&A) completion in China and scrutinizes the influence of global and domestic economic conditions through survival analysis. By utilizing data from 3227 domestic M&A transactions from 1998 to 2024, this study employs quantitative survival analysis and the Cox proportional hazards model to evaluate how economic indicators shape M&A success rates. Notably, increases in the industrial production index (IPI) and producer price index (PPI) are positively associated with an increased likelihood of completion, reflecting how economic expansion fosters financial stability, strengthens firm capacity, and facilitates deal finalization. In contrast, rising global policy uncertainty, as captured by the global economic policy uncertainty (EPU) index, significantly reduces the likelihood of M&A completion by amplifying valuation ambiguity, negotiation frictions, and regulatory risks. Unexpectedly, the global economic growth—represented by the global real economic activity (GREA) index—correlates with a decreased likelihood of success in domestic M&A, potentially due to a shift in focus toward international opportunities and rising costs of domestic operations. Furthermore, the KaplanMeier estimator of the hazard function reveals a nonlinear curve depicting the likelihood of deal completion over time, emphasizing fluctuations in the probability of success. Our results indicate that the time elapsed from the announcement of a deal can provide crucial information on the ex-ante probability of its success or failure, highlighting the importance of considering the temporal aspect of the deal.